De Albert Camus a Maïssa Bey, miradas cruzadas, de una Argelia a otra - Castellani, Jean-Pierre (Universidad Nacional del Litoral, 2010)
In her book L’ombre d’un homme qui marche au soleil (2004) the Algerian writer Maïssa Bey pays a moving tribute to the French writer Albert Camus. She shows that today, Algerian intellectuals are indeed reconsidering his work and his personnality, through a less passionate reading of his books, leaving aside the polemics created by Camus stance during Algeria war of independence. The objective is hence to gauge Camus influence on Algeria’s litterature from the examples shown by MB.